Employment in the EU countries: a panel data analysis - Larisa STĂNILĂ; Mădălina ANDREICA; Amalia CRISTESCU (Theoretical and Applied Economics, 2013)

(untitled)
This paper examines the evolution of some important macroeconomic indicators for the EU analysing the changes caused by the crisis in the last years and tries to find which one of them is affecting the employment rate. We therefore employ a panel data approach, considering the 27 countries. The econometric results showed that the variables considered in the model are statistically significant and the estimators are robust (with only one exception – the trade openness variable, which was excluded from the robust estimation).